PEMBERDAYAAN PETERNAK MISKIN (STUDI KASUS PEMBERDAYAAN PETERNAK ITIK DI DESA BANGUN PURBA KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU PROVINSI RIAU) - Hamdi Sari Maryoni; Kiagus Muhammad Basriwijaya (Jurnal Peternakan Lingkungan Tropis, 2019)
Livestock industry have been playing the important in national economics. Problem faced by livestocks are capital problem, acces material, acces technology, networking in institutional livestock group, low human resources, marketing egg duck. The Community Development Research executed in three phase, there are social mapping, evaluate the program and empowerment research livestock poor in improving well-being livestock. Research method used is qualitative method. Technique of qualitative data collecting used are observation, in depth interview and Focus Group Discussion (FGD). Problem identified with the descriptive analysis, program compilation execused with livestock community in FGD forum. Result of research indicate that poorness that happen at breeder duck in Bangun Purba Village because of breeder duck enterprise to have a loss effect avian influenza epidemic, tied pengijon/tengkulak, scale of is effort inefficient and downhill (it) investment to effort duck livestock. The Empowerment Program conducted by (1) Revitalization of Farmer Group, (2) Network Development and (3) Empowerment Mertelu Sistem.